2021
DOI: 10.1097/mat.0000000000001602
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Extracorporeal Membrane Oxygenation for Covid-19 Does Not Pose Extra Risk to Transport Team

Abstract: for the Covid-19 CritiCaL Care ConSortium Previous experience has shown that transporting patients on extracorporeal membrane oxygenation (ECMO) is a safe and effective mode of transferring critically ill patients requiring maximum mechanical ventilator support to a quaternary care center. The coronavirus disease 2019 (COVID-19) pandemic posed new challenges. This is a multicenter, retrospective study of 113 patients with confirmed severe acute respiratory syndrome coronavirus 2, cannulated at an outside hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…That report did not specify what, if any, testing measures were put in place for the ECMO team members, so some may have been contaminated and remained asymptomatic. The aforementioned reports 28,29 are in accordance with a multicentric study that suggested mobile ECMO does not add additional hazard to the ECMO transport team 30 …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…That report did not specify what, if any, testing measures were put in place for the ECMO team members, so some may have been contaminated and remained asymptomatic. The aforementioned reports 28,29 are in accordance with a multicentric study that suggested mobile ECMO does not add additional hazard to the ECMO transport team 30 …”
Section: Discussionsupporting
confidence: 82%
“…The aforementioned reports 28,29 are in accordance with a multicentric study that suggested mobile ECMO does not add additional hazard to the ECMO transport team. 30 Another study demonstrated a very low risk of COVID-19 contamination to EMS and reported an incidence of 0.57 infections/ 10,000 person-days over a similar study period. 31 Our study, however, is based on a higher number of COVID-…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Adequate training, appropriate infection prevention control measures, personal protective equipment (PPE), and ambulance disinfection are essential for patient and medical personnel safety. Other transport safety suggestions may include adequate ventilation of the transport platform, the use of dedicated routes for patients with COVID-19 during intrahospital patient transport, and an additional filter on the expiratory limb of the transport ventilator [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Obwohl solche Transporte durch die PSA eine deutlich höhere Belastung für das Transportteam darstellen, sind sie unter Beachtung entsprechender Schutzmaßnahmen sicher durchführbar (Abb. 3 ; [ 15 ]).
…”
Section: Durchführung Des Intensivtransportsunclassified